Seeking for Identity in the Novel Less (2017) by Andrew Sean Greer - Irza Ade Suarni; An Fauzia Rozani Syafei (English Language and Literature, 2023)
This thesis is an analysis of the Novel Less (2017) by Andrew Sean Greer. The purpose of this analysis is to find out to which setting and conflict (plot) reveal the efforts of the main character in the Novel Less in dealing with problems that come to him by trying to fight and rise from failure. This analysis is related to the concept of life instinct proposed by Sigmund Freud and self-determination by Ryan and Deci. The result of this analysis shows that the main character has self-motivation and goals in his life as shown through his action in seeking his identity.